2020
DOI: 10.1021/acs.jctc.0c00719
|View full text |Cite
|
Sign up to set email alerts
|

Charge-Changing Perturbations and Path Sampling via Classical Molecular Dynamic Simulations of Simple Guest–Host Systems

Abstract: Currently, two different methods dominate the field of biomolecular free-energy calculations for the prediction of binding affinities. Pathway methods are frequently used for large ligands that bind on the surface of a host, such as protein–protein complexes. Alchemical methods, on the other hand, are preferably applied for small ligands that bind to deeply buried binding sites. The latter methods are also widely known to be heavily artifacted by the representation of electrostatic energies in periodic simulat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
41
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(41 citation statements)
references
References 62 publications
(143 reference statements)
0
41
0
Order By: Relevance
“…Interestingly, the other two perturbations involving a charge change result in slightly different free-energy differences. It is important to note that such perturbation calculations suffer from various artifacts, including one related with the choice of the cutoff scheme used in simulations (the DSM term in ref ( 66 )). As different cutoff schemes were used when simulating with the two simulation packages (group-based and atom-based for GROMOS and GROMACS), contributing differently to the abovementioned artifact, the observed discrepancies in the free-energy differences are not surprising.…”
Section: Resultsmentioning
confidence: 99%
“…Interestingly, the other two perturbations involving a charge change result in slightly different free-energy differences. It is important to note that such perturbation calculations suffer from various artifacts, including one related with the choice of the cutoff scheme used in simulations (the DSM term in ref ( 66 )). As different cutoff schemes were used when simulating with the two simulation packages (group-based and atom-based for GROMOS and GROMACS), contributing differently to the abovementioned artifact, the observed discrepancies in the free-energy differences are not surprising.…”
Section: Resultsmentioning
confidence: 99%
“…However, it has been observed that the binding free energy computed with path sampling did not converge to the same end result as those done alchemically and corrected with the Rocklin correction. 49 However, one study has also shown that they can give similar results. 50 One explanation for this discrepancy would be that the self-interaction term would be size-dependent when the species of opposite charge cannot sample the same configurational space.…”
Section: Discussionmentioning
confidence: 91%
“…In the SAMPL7 TrimerTrip host-guest blind challenge, utilization of the AMOEBA force field shows excellent results with 7/8 samples having errors within 2 kcal/mol ( Laury et al, 2018 ; Shi et al, 2020 ; Amezcua et al, 2021 ). The commonly used approach to maintain charge neutrality through co-alchemical ions is shown not to fully eliminate charge artifacts in periodic simulation boxes due to localized differences in electrostatic potentials and solvent densities for the distant ion and bound ligand ( Ohlknecht et al, 2020b ). Continuum-electrostatics calculations ( Ohlknecht et al, 2020a ) and the “Warp-Drive” ( Ekimoto et al, 2018 ) method of simultaneously perturbing the protein-ligand complex and a distant unbound ligand are proposed to more accurately correct for finite-size effects.…”
Section: Free Energy Calculation Approachesmentioning
confidence: 99%